2016
DOI: 10.1007/s10238-016-0431-4
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate treatment provokes apoptosis of proliferating keratinocyte in psoriasis patients

Abstract: Psoriasis is a chronic inflammatory skin disease characterized by hyper proliferation of keratinocytes. Recent data show that the epidermis thickening in psoriasis may be related to imbalance of homeostasis caused by abnormal apoptotic process. Maintenance of keratinocyte apoptotic process is very important in psoriasis. Methotrexate (MTX) has been used for many years to restore the normal skin in psoriasis condition. However, the exact mechanism of MTX in psoriasis condition is poorly understood. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…Apoptosis, a genetically controlled cell death program (Shichiri et al 2000), plays a pivotal role in the development, differentiation, and defense of skin homeostasis (Elango et al 2017, Lerman et al 2011. Recent data showed that hyperproliferation of keratinocytes and decreased epidermal keratinocyte apoptosis (via the action of inflammatory mediators) are principal clinical aspects of psoriasis (Deng et al 2016, Elango et al 2017, Lerman et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, a genetically controlled cell death program (Shichiri et al 2000), plays a pivotal role in the development, differentiation, and defense of skin homeostasis (Elango et al 2017, Lerman et al 2011. Recent data showed that hyperproliferation of keratinocytes and decreased epidermal keratinocyte apoptosis (via the action of inflammatory mediators) are principal clinical aspects of psoriasis (Deng et al 2016, Elango et al 2017, Lerman et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…EGF regulates keratinocyte growth, proliferation, and differentiation by binding to epidermal growth factor receptor (EGFR) and maintain high proliferative state 26,27 . Apoptosis has been proposed as a mechanism that disrupts abnormal epidermal thickness in psoriasis 28 . To investigate the role of PPL on EGF-induced hyperproliferation, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was performed in the presence of EGF, which showed that PPL effectively reduced the EGFstimulated cell viability of keratinocytes at both 24 ( Fig.…”
Section: Inhibitory Effects Of Ppl On Keratinocyte Hyperproliferationmentioning
confidence: 99%
“…In PsO, a dysregulation of cytochrome c has been demonstrated. Indeed, a higher serum and mitochondrial levels were observed compared to healthy skin; this contributes to epidermal hyperplasia ( 37 ). Concerning PsA, the result is synovial inflammation and joint destruction ( 38 ).…”
Section: Potential Role Of Cytochrome C and Tryptase In Psoriasis Andmentioning
confidence: 99%